Pokolenie przegranych? Kondycja psychospołeczna młodzieży w Europie Środkowo-Wschodniej - Długosz, Piotr (Zeszyty Pracy Socjalnej, 2017)
The following article aims at verifying the question of psycho-social condition of youth. In the discourse on youth, theses about increasing marginalization of youth, entering adulthood being hindered and the phenomenon of psycho-wave appear. In order to verify the researched issue, survey method was used. The data was collected by means of auditorium questionnaire. The research sample was of quota character. The research sample in Poland consisted of 3479 respondents, 1289 in Ukraine and 359 in Hungary. The gathered observations refute the theses about the worsening of their psycho-social condition. Youth from all the researched countries in comparison with the generation of their parents evaluate their chances of getting a good education, a satisfying job, achieving high social status and social standing better. Higher skepticism is observed in terms of starting a family and deriving satisfaction from their lives. The researched youth are also satisfied with their lives and evaluate their future positively. The youth from post-transformational societies are of good psycho-social condition and instead of creating a problem for the society, they will constitute their vital resources.
Keywords: youth; psycho-social condition; psycho-wave effect; East-Central Europe